Differences in the carbon flows in the benthic food webs of abyssal hill and plain habitats. (24th March 2017) - Durden, Jennifer M.; Ruhl, Henry A.; Pebody, Corinne; Blackbird, Sabena J.; van Oevelen, Dick
Abstract: Inputs of detritus from the surface ocean are an important driver of community dynamics in the deep sea. The assessment of the flow of carbon through the benthic food web gives insight into how the community is sustained, and its resilience to fluctuations in food supply. We used a linear inverse model to compare the carbon flow through the food webs on an abyssal hill and the nearby plain at the Porcupine Abyssal Plain sustained observatory (4850 m water depth; northeast Atlantic), to examine the partitioning of detrital input in these substantially different megafaunal communities. We found minimal variation in carbon flows at the plain over two years, but differences in the detrital inputs and in the processing of that carbon input between the hill and plain habitats. Suspension feeding dominated metazoan carbon processing on the hill, removing nearly all labile detritus input to the system. By contrast, half of all labile detritus was deposited and available for deposit feeders on the abyssal plain. This suggests that the biomass on the hill is dependent on a more variable carbon supply than the plain. The presence of millions of abyssal hills globally suggests that the high benthic biomass and respiration, and reduced deposition of detritus may be pervasive, albeit with varying intensity.